PERAWATAN LUKA INFUS TERHADAP KEJADIAN PHLEBITIS - Rudi Hamarno; Tutik Herawati; Bramunanto Suprayoga (Jurnal Keperawatan Terapan, 2019)
Prevention of phlebitis is not only focused on infusion, but afterwards infusion must be protected entirely from complications. Preventing and minimizing the effects of intravenous therapy, especially the occurrence of phlebitis, infusion treatment must be optimally sought. Nurses who pay attention to aseptic principles can reduce phlebitis events (Brunner and Suddarth, 2001). The purpose of this study was to determine The Effect of Infusion Wound Care With On Phlebitis Incidents At The RSUD dr. R. Soedarsono Pasuruan City. The research design used was pre-experimental research with a sample size of 20 people and using purposive sampling technique. Data collection method used interview and observation and analysed by Chi Square test. The results of the study in the treatment group showed that the incidence of phelbitis in hospitalized patients was 10 percent phlebitis and 90 percent did not occur phlebitis. In the control group 70 percent occurred phlebitis and 30 percent did not occur phlebitis, and a significant value of 0.006 which stated that there was the effect of infusion treatments with on phlebitis incidents to inpatients. Suggestions that can be submitted to next researcher are the biggest factor causing phlebitis and examine other prevention of phlebitis.